Memahami dan Mengembangkan Potensi Anak Berbakat: Pendekatan Pendidikan dan Pendampingan Sosial-Emosional - Syukri Syukri; Badri Badri; Robi Agus Pratama; Yohana Dwi Putri; Rinaldho Rinaldho; Novrian Ramadhan (STIKes Ibnu Sina Ajibarang, 2024)
Every child is born with unique characteristics that are viewed favorably by the Creator. No child is born without a life plan from God. The presence of a child brings happiness to parents who have longed for their arrival. Each child has different abilities and characteristics, even twins. This uniqueness requires parents to provide treatment that is appropriate for the child's condition. Children with above-average abilities are known as gifted children. In the field of education, especially in elementary schools, it is important for teachers to identify gifted children. A teacher's knowledge of the criteria for gifted children is crucial for determining the appropriate handling, as gifted children require special treatment to optimally develop their talents. Gifted children often exhibit unique learning styles, talents, and characteristics that necessitate individualized learning approaches. Despite their high intelligence, gifted children may also experience difficulties with social and emotional tasks. Therefore, they need a conducive learning environment and counseling services to support their social-emotional development. The development of creativity and moral education also plays a significant role in shaping the personality of gifted children.